If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7r + 43 = 1 Reorder the terms: 43 + 7r = 1 Solving 43 + 7r = 1 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-43' to each side of the equation. 43 + -43 + 7r = 1 + -43 Combine like terms: 43 + -43 = 0 0 + 7r = 1 + -43 7r = 1 + -43 Combine like terms: 1 + -43 = -42 7r = -42 Divide each side by '7'. r = -6 Simplifying r = -6
| 25(x+7)=9x-2 | | -3=2y+35 | | (3/7)m=6 | | X-8=2+7x-5x | | P(x)=15x-125 | | 2x+x=11+3-4x | | s+3t=-4 | | 75-u=272 | | 21x^2-76x+20=0 | | 12x+18=56-7x | | 1/5x-5/6=3/4x-5 | | 2z+x=8z-12 | | 2-2x=-7x | | 12+4z=8(z-1) | | -5b= | | x^2=100-2x^2 | | -8g+6=30 | | 15x^2=8x-16 | | -68=-5x-6x+9 | | 4x-1/2=10 | | 18x+18-47x=255 | | 3x-5x-40= | | 4x-2+6=7x-3 | | 3x+y=w | | 5x+5+25=0 | | -3h=3h-7 | | -3(2x-4)=-3x | | 4(x-90)=20 | | 9q-3+8q= | | x/a=y/a | | -50=5x+3x-2 | | 6u1/2-3u3/4 |